TANGGUNG JAWAB DEALER TERHADAP INDENTOR DALAM PERJANJIAN JUAL BELI MOBIL DENGAN SISTEM INDEN - Wa Ode Zamrud; La Ode Muhammad Muskur; Muhammad Syarifuddin; Devi Sari Angraini (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
In this journal, the author discusses the issue of dealer responsibility for indentor in car buying and selling agreements with indent systems. The purpose of writing this journal is to find out the implementation of the sale and purchase agreement with the indent system at PT. Hadji Kalla Toyota Baubau in addition to knowing how the dealer's responsibility if the car received indentor is not in accordance with the promised. This research is an empirical legal paper and uses a qualitative approach with primary data sources obtained from interview results and secondary data obtained from the literature study process. The data analysis method used in this study is qualitative descriptive. The results showed that in the implementation of buying and selling consumers were given an order form in the form of Vehicle Order Letters and paid a finished mark of Rp. 5,000,000-, for a cash-indented car advance of at least 30% while the credit indent was at least 25% of the price of the car ordered. The dealer's responsibility when default is if the car received late the dealer always provides the latest information about delivery, If there is a hidden defect in the dealer's car replaces the damage with factory standards, if the car received does not match the color ordered the dealer offers the car with the same type of different color. PT. Hadji Kalla Toyota Baubau should write clearly in the Vehicle Order Letter important points such as certainty of delivery time, vehicle repayment deadline, and risk of violation of these points and provide assurance to consumers in purchase in indent by maintaining communication between the dealer and the manufacturer to reduce the risk of delays and errors in delivery and the quality of goods (no damage) of the vehicle.